صورة الاستدانة في الصكوك الوقفية: دراسة فقهية = Modern form of borrowing in Waqf Sukuk: a juristic study - Mohd Zain, Nor Amni Bazilah; Abdul Aziz, Akhtarzaitie (IIUM Press, International Islamic University Malaysia, 2020)
إن الوقف له دور مهم عبر التاريخ الإسلامي، وقد بدأ مشروعية الوقف منذ عهد النبي ﷺ، وقد بذل العلماء القدامى والمعاصرون الجهد لإيجاد حكم شرعي في كل ما تتعلق بالوقف. وتهدف هذه الدراسة إلى بيان مفهوم الاستدانة في الوقف ومشروعيتها، وبيان آراء الفقهاء القدامى المعاصرين في الاستدانة في الوقف، مع توضيح الصور والضوابط الشرعية التي تتعلق بها على نحو وافٍ. وقد توسَّلت الباحثة المنهجين الاستقرائي والتحليلي، ونظراً لكثرة آراء الفقهاء في الاستدانة في الوقف؛ فثمّة قولان للعلماء: القول الأول، يرى عدم جواز الاستدانة في الوقف، والثاني يرى أن ذلك يجوز بالضوابط. ونظراً لكثرة الضوابط الشرعية للاستدانة؛ فقد اختارت الباحثة الضوابط المتفق عليها بين الجمهور، واقتصر الاختلاف على مسألتين: مسألة إذن الواقف، ومسألة إذن القاضي، وبيَّنت الدراسة أن صور الاستدانة لإعمار الوقف تنقسم إلى نوعين رئيسيين: الطرق القديمة، ومنها الاستدانة من بيت المال أو المال العام، والاستدانة من مال الناظر، والاستدانة من مال وقف آخر، وتعد الصكوك الوقفية من طرق الاستدانة الحديثة لتمويل المشروعات الوقفية، وختمت الباحثة بعرض الضوابط الشرعية للاستدانة في الوقف. ************************************************************************** Waqf is an Islamic philanthropy instrument which started during the time of Prophet Muhammad (bless and peace be upon him). Muslim scholars have a lengthy discussion on the legality of Waqf. The objective of this research is to examine the concept of borrowing in relation to Waqf and their legitimacy either from classical or contemporary opinions of Muslim scholars. This research focuses on two main opinions among Muslims scholars. One group of Muslim scholars is in the opinion that it is not permissible to borrow from Waqf. Another group of Muslim scholars said it is permissible subjected to certain regulations. This research describes the regulations that have been agreed among the majority of Muslim scholars. The borrowing from Waqf is subjected to two main conditions i.e. (i) a permission from Waqf donors, and (ii) a permission from judges. The practicality in borrowing from Waqf is divided into two types i.e. (i) old methods and (ii) the modern method. Old methods of borrowing from Waqf consist of (i) borrowing from baitulmal or public funds, (ii) borrowing from nazhir of Waqf, and (iii) borrowing from another fund of Waqf. The modern method of borrowing of Waqf is known as Waqf-sukuk which is to finance Waqf-based projects.